ELS issues in robotics and steps to consider them. Part 1: Robotics and employment. Consequences of robotics and technological change for the structure and level of employment - Melanie Arntz; Terry Gregory; Ulrich Zierahn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
Recent advances in the field of digitization and robotics, such as driverless cars, largely autonomous smart factories, service robots or 3D printing, give rise to public fears that technology may substitute for labor on a grand scale. Against this background, the report reviews the existing literature on the employment effects of technological change to derive policy implications and to identify open research questions. We highlight that past technological change has mostly affected the structure of employment, but had only little or even positive effects on the level of employment. In particular, the recent computerization was associated with a declining share of routine-task-intensive middle-skill jobs, while, on net, it has led to an increase of labor demand. The scientific evidence further suggests that technological change in the foreseeable future will continue to mostly affect the structure of labor demand without necessarily changing total employment much. As we argue, the main challenge for the future of work lies in coping with rising inequality, as technological change creates both winners and losers. Policy makers should focus on the qualifications of the workers to ensure that workers' skills match future skill requirements. However, we highlight that there remain many open research questions regarding the need for policy responses, the effectiveness of alternative measures, as well as which skills will be required in the near future.
Additional information: This report has been produced for the Partnership for Robotics SPARC in Europe via RockEU: Robotics Coordination Action for Europe, a Coordination and Support Action (CSA) project that has received funding by under the EU FP7 research and innovation programme (grant agreement 611247). - RockEU: Robotics Coordination Action for Europe. Grant Agreement Number: 611247. 17.01.2013 - 16.07.2016. Instrument: Coordination and Support Action. Deliverable D3.4.1. - part 1.
Keywords: 330